Modern ERP : Select, Implement, and Use Today's Advanced Business Systems - Bradford, Marianne (North Carolina State University, North Carolina, 2008)
Modern ERP can be used in an undergraduate or graduate enterprise resource planning systems course or to support an ERP module in information systems, accounting, business, or supply chain courses. This third edition continues to be vendor-agnostic and has been substantially revised to keep pace with advances in the ERP marketspace. New topics include cloud computing, mobility, and business analytics, while ERP security, ERP risk management, databases, and supply chain have been expanded. Innovative graphics and ERP screenshots have been incorporated to further aid in the learning process.
Keywords: Management -- Business